Isolable Silylene Ligands Can Boost Efficiencies and Selectivities in Metal‐Mediated Catalysis - Zhou, Yu‐Peng; Driess, Matthias (Angewandte Chemie International Edition, 2019)
A significant number of isolable silylenes are currently known. They have quickly developed from laboratory curiosities to useful ligands in metal‐mediated homogeneous catalysis. This includes their utilization in various catalytic transformations, such as C−C cross‐coupling, cyclotrimerization, hydroformylation, borylation, deuteration, hydrosilylation, amination, hydrogenation, and transfer semi‐hydrogenation reactions. Recent studies suggest that the silylene ligands surpass the steering properties of their phosphine and N‐heterocyclic carbene (NHC) analogues and provide excellent chemo‐, regio‐, and stereoselectivites. Mechanistic studies suggest that their promoted performance of metal‐mediated catalytic transformations results from a strong σ‐donor character along with cooperative effects of their SiII centers. This Minireview covers the most recent advances in the field. No longer laboratory curiosities: Stable silylenes are a versatile family of powerful steering ligands that increase catalytic activity and selectivity. This Minireview covers the recent progress of silylene ligands in homogeneous catalysis.